Broadcast journalism : techniques of radio and television news - Stewart, Peter; Alexander, Ray (N. York Routledge, 2022)
"Now in its 8th edition, Broadcast Journalism continues to be an essential text on the production of news broadcasting and the practical skills needed. Including not only basic techniques and classic examples for the production of radio and TV news, the book also delves into new technology and the latest case studies. The fundamental skills of interviewing, news writing and production now have to cope with the prevalence of fake news and deep fakes and verifying content in an endless flow of social media. This edition also includes newsgathering with mobile devices, live reporting and using data and graphics. There are dozens of new images and links for downloads and further reading, plus end-of-chapter exercises and tutor notes. This continues to be an indispensable textbook for broadcast journalism and communications students looking for an in-depth guide to the industry"--
Do you want the job? -- Ethics. Law. Fakes & fabrications (biggest now - 35 pages) -- Story types for broadcast journalism -- News channels, programmes and streams -- Where news comes from -- Choosing and chasing the story -- Setting up the interview -- The interview -- Writing basics -- Writing for news -- Broadcast news style book -- Putting the show together -- News anchors and presenters -- On air -- Newsreading -- Story treatment -- Recording -- Editing -- The studio -- Television newsroom production -- Writing television news -- Gathering television news. -- Getting the shots -- Editing the pictures and sound -- Live TV reporting -- Data, graphics and visuals -- The television news studio and presentation.
Includes bibliographical references and index.
Keywords: Broadcast journalism; Journalism; Broadcast